2001
DOI: 10.2135/cropsci2001.4141066x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Environmental Effects on Grain Yield and Quality of Oat Grown in North Dakota

Abstract: The grain yield and quality determine much of the value of an oat (Avena sativa L.) crop to the producer. This study investigated effects of genotype and environment on grain yield and quality. Twelve oat genotypes were grown during 3 yr at four locations in North Dakota where detailed environmental data were being collected. Grain yield, test weight, groat percentage, groat weight, and groat composition (protein, oil, β‐glucan, and starch concentrations) were evaluated. Results were subjected to analysis of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
106
0
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 32 publications
13
106
0
11
Order By: Relevance
“…The results were contrasting: b-glucan was found to be affected by a reduced availability of water (Peterson 1991;Brunner and Freed 1994), or positively correlated to the amount of precipitation in July and August, and to warmer temperatures (Doehlert et al 2001). Previous data also showed that both oat genotype and agronomic practises, as seeding season and rotation, can be important determinants of the variability of protein and b-glucan (Redaelli et al 2009).…”
Section: Discussionmentioning
confidence: 97%
“…The results were contrasting: b-glucan was found to be affected by a reduced availability of water (Peterson 1991;Brunner and Freed 1994), or positively correlated to the amount of precipitation in July and August, and to warmer temperatures (Doehlert et al 2001). Previous data also showed that both oat genotype and agronomic practises, as seeding season and rotation, can be important determinants of the variability of protein and b-glucan (Redaelli et al 2009).…”
Section: Discussionmentioning
confidence: 97%
“…From the 1970s onwards, several breeding program partnerships were established between the United States and Brazilian research institutions; these programs introduced the sources of resistance mainly to leaf and stem rust in oat (Federizzi et al, 2005). Leaf rust is a major disease of oat (Zambonato et al, 2012), causing reduction in its grain quality (Doehlert et al, 2001). It was assumed that genetic progress in grain yield and hectoliter weight was associated with fungicide use on aerial plant parts of oat cultivars in RS.…”
Section: Introductionmentioning
confidence: 99%
“…avenae Fraser & Led.,), é a moléstia mais importante que ataca a cultura da aveia, ocorrendo em praticamente todas as áreas em que a aveia é cultivada (SIMONS & MURPHY, 1961). A moléstia vem sendo apontada como um dos principais fatores limitantes para a expansão da área cultivada com o cereal, uma vez que a mesma pode ocasionar perdas no rendimento, por reduzir o peso e a qualidade dos grãos, mesmo em plantas moderadamente atacadas (DOEHLERT et al, 2001;LORENCETTI et al, 2004;BENIN et al, 2005).…”
Section: Introductionunclassified